The role of intestinal ultrasound in diagnostics of bowel diseases - Andrzejewska, Magdalena; Grzymisławski, Marian (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Intestinal ultrasound is a safe and inexpensive method that allows visualisation of the gastrointestinal tract and detection of abnormalities. This examination involves the use of two different ultrasound transducers: a low-frequency convex probe and high-frequency linear probe. When needed, the performance of these methods can be enhanced by the use of contrast media or Doppler techniques. Intestinal ultrasound is mostly utilised for the diagnosis and follow-up of patients with inflammatory bowel diseases, helping to avoid frequent use of invasive and expensive diagnostic procedures and leading to early implementation of suitable treatment. This technique can also serve to detect other pathologic conditions that are present in the gastrointestinal tract. It is a promising method with high sensitivity and specificity, which has gained popularity in recent years and has the potential to become the method of choice in the diagnostics of many intestinal disorders.